INTERPERSONAL RELATIONSHIP MANAGEMENT IN SPORT COACHING PROCESS - Putut Marhaento (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
When a person decides to choose the profession as a coach, he/she has to think that be a coach is not only how to influence the foster children so that they can brought to the settled purposes but it is more than that, a coach has to influence the surrounding environment in order to optimize the children activities better in the practice or competition. In the sport world, the process of influencing others include the aspect of make a decision, motivation technique, giving feedback, interpersonal relationship decision, and guiding the group confidently. A leader is not only known about the targets achieved but also the steps that needed to gain those. One of the coach's duty as a professional person is he/she must able to play role as a public relations. For that reasons, coaches have to have interpersonal skills so that they can work more effective with the coach staff, administrator, energ'!t medical, match official, athlete's parent and mass media. Keywords: management, interpersonal relationship, coaching process